Commissioning of a photoelectron spectrometer for soft X‐ray photon diagnostics at the European XFEL. (15th May 2019) - Laksman, Joakim; Buck, Jens; Glaser, Leif; Planas, Marc; Dietrich, Florian; Liu, Jia; Maltezopoulos, Theophilos; Scholz, Frank; Seltmann, Jörn; Hartmann, Gregor; Ilchen, Markus; Freund, Wolfgang; et al.
Abstract : Commissioning and first operation of an angle‐resolved photoelectron spectrometer for non‐invasive shot‐to‐shot diagnostics for photon energy and polarization at the European XFEL soft X‐ray beamline SASE3 are described. Abstract : Commissioning and first operation of an angle‐resolved photoelectron spectrometer for non‐invasive shot‐to‐shot diagnostics at the European XFEL soft X‐ray beamline are described. The objective with the instrument is to provide the users and operators with reliable pulse‐resolved information regarding photon energy and polarization that opens up a variety of applications for novel experiments but also hardware optimization.